2019
DOI: 10.1108/jpbm-02-2018-1747
|View full text |Cite
|
Sign up to set email alerts
|

Brand community identification matters: a dual value-creation routes framework

Abstract: Purpose A brand community consists of relationships between a brand and consumers; community members’ identification with the brand community is a central characteristic of the community. This study aims to provide a comprehensive conceptual framework to investigate how and why such identification-based relationships yield firm- and member-level benefits to participants in the brand community. Design/methodology/approach This cross-sectional study analyzes data collected through a questionnaire survey of memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 125 publications
2
24
0
1
Order By: Relevance
“…Wirtz et al (2013) argue that brand identification facilitates consumers' integration within the OBC. Empirical findings also pinpoint brand identification as an antecedent of consumers' willingness to participate in a social brand community (Chang et al, 2019). For example, in the context of car communities, Algesheimer et al (2005) posit that customers' previous relationships with a car brand exert an influential role to the identification and engagement with the community.…”
Section: H1 Community Identification Positively Influences Cbementioning
confidence: 96%
“…Wirtz et al (2013) argue that brand identification facilitates consumers' integration within the OBC. Empirical findings also pinpoint brand identification as an antecedent of consumers' willingness to participate in a social brand community (Chang et al, 2019). For example, in the context of car communities, Algesheimer et al (2005) posit that customers' previous relationships with a car brand exert an influential role to the identification and engagement with the community.…”
Section: H1 Community Identification Positively Influences Cbementioning
confidence: 96%
“…Considering the online context, a recent study found that consumer identification with a brand is stronger when consumers perceive it as more prestigious and more humanlike (Tuškej and Podnar 2018). The same study also showed a positive impact of consumer identification with a brand on their engagement with the brand, while a very recent study found that when customers' identification with a brand community becomes salient, they strengthen their emotional attachment to the brand and improve their centrality in the network (Chang et al 2020). In addition to company/brand performances, community identification can provide benefits for consumers in terms of a stronger personal brand.…”
Section: Introductionmentioning
confidence: 93%
“…This contributes to the brand relationship and brand community management literature in an important way. Despite the three central relationships that influence consumer behaviour in brand communities, namely customer-to-brand, customer-to-customer and customer-to-the community (Chang et al 2020), most of the studies have focused on the former with a lack of attention on the customer-to-customer relationship (Luo et al 2016).…”
Section: Community Relationships and Identificationmentioning
confidence: 99%
“…Previous research has noted that identification is one of the key antecedents for brand community engagement (Chang et al , 2019; Chen et al , 2018; Khan and Khattak, 2017; Mousavi et al , 2017). Identification occurs when one perceives a sense of “oneness or belongingness to a group, where an individual defines him or herself in terms of the group of which he or she is a member” (Demiray and Burnaz, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%